People with intellectual disability in Ireland are still dying young. Issue 4 (30th December 2020) - Doyle, Anne; O'Sullivan, Michael; Craig, Sarah; McConkey, Roy
Abstract: Background: People with intellectual disability die younger than their non‐disabled peers. In recent years, greater attention has been paid to closing the gap. However, evidence that this is being achieved is limited by the dearth of longitudinal, national data. Method: Over 4, 000 decedents identified in the Irish National Intellectual Disability Database from 2001 to 2016 were compared to deaths in the general population based on age and gender profiles using death rates and standardised mortality ratios. A binary logistic regression analysis also identified the characteristics of persons who had a higher risk of dying. Results: Irish people with intellectual disability die younger and have a higher rate of death than their non‐disabled peers. Nor has the gap between their mortality and that of the general population closed in recent years. Conclusions: More concentrated effort is needed in Ireland on promoting equitable access to health services for people with intellectual disability.